Keratoma Can Be Treated Successfully With Simple Hoof Surgery: Hoof resection as a simple way to remove keratoma in a horse - JAWORSKA, J. (Journal of the Hellenic Veterinary Medical Society, 2018)
Keratoma is a very rare condition, but if occurs often results in lameness in a horse. Despite its rarity, it is one of the most common reasons to perform foot surgery, because the surgery is the only effective treatment. In this case report diagnosis was based on radiographs of the foot and histopathological findings. There was a repeated debridement of the keratoma performed in the patient. After all the keratoma was removed the mare showed no more lameness.